MENGELOLA PENDAPATAN KAMAR HOTEL YANG OPTIMUM (YIELD MANAGEMENT) - Hermawan, Budi (Sekolah Tinggi Pariwisata AMPTA, 2010)
The market is always changing and increasing competition. In this condition, the hotel needs to improve responsiveness to the environment to service. Hotels should be able to establish a policy with the best results. Yield management offers a concept for each hotel is able to put himself in the best position in the changing environment. Revenues need to be managed well for a more popular method is called yield management or revenue management Currently, yield management, has become a very important innovation in the hospitality industry. The main objective of yield management is to maximize the occupancy room and at the same price achieved average room rate is high. The rooms are the same product, but have different market segments, both used by the guest or guest tours individual. Each market segment may be subject to different prices for the same period. Demand for each segment in the future, have a fairly high level of uncertainty in thiscase, management does not know how much and when the individual guest is coming. Individual guest room reservations typically do on arrival or a few days prior to say, while guest tour groups generally pay full price and keep the rooms are not already sold to the tourist gueist at cheap prices or discounts. Profit oriented hotel management and have broad freedom of action to increase revenue at the optimum level of demand for rooms is very high. This is to compensate low income or cover losses in the period of very Iow occupancy rates, where rooms are sold at discount in nearly all segments. Room sales management to achieve optimum opinions need to plan how many rooms are sold at a discount and how many rooms were sold at full price. In addition . to avoid loss of revenue due to cancellation of booking rooms during periode of high demand for rooms, management needs to accept room reservations exceeds the number of rooms available for sale. KEY words: yield management, discount price, full price. Peak season , low season, overbooking.